Need analysis of a vertebrate electronic atlas as a biology instructional media - Ardiana, Rinata (Universitas Negeri Padang, 2023)
The purpose of this study was to analyze the needs of teachers and students in develop vertebrate e-atlas as biology learning media on animalia material. Based on the first step of the ADDIE development model, analysis, the requirements analysis is conducted. The study was done to find out the problems regarding the learning media used and what media are needed. 24 students from the class X IPA 3 served as the study's subjectsand 1 biology teacher at SMA Panca Marga 1 Lamongan. Guidelines for interviews and questionnaires served as the research instruments. The data analysis method employed descriptive analysis of the interview findings and sought the mean of the questionnaire responses, which were then qualitatively characterized. The results of the needs analysis obtained from interviews with biology teachers stated that it is very necessary to develop a vertebrate e-atlas to provide a variety of existing learning media. The results of the analysis of student needs showed that as many as 92.8% of students found it easier to absorb subject matter using instructional media and as many as 85.7% of students were interested in developing e-atlas vertebrate learning media as biology learning media in animalia material. It may be inferred from the research that there is a need to develop vertebrate e-atlas media in learning biology, especially in animalia material.